Decreased CSF Dynamics in Treatment-Naive Patients with Essential Hypertension: A Study with Phase-Contrast Cine MR Imaging - Ma, L.; He, W.; Li, X.; Liu, X.; Cao, H.; Guo, L.; Xiao, X.; Xu, Y.; Wu, Y. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Arterial sclerosis resulting from hypertension slows CSF transportation in the perivascular spaces, showing the intrinsic relationship between the CSF and the blood vasculature. However, the exact effect of hypertension on human CSF flow dynamics remains unclear. The present study aimed to evaluate CSF flow dynamics in treatment-naive patients with essential hypertension using phase-contrast cine MR imaging.MATERIALS AND METHODS: The study included 60 never-treated patients with essential hypertension and 60 subjects without symptomatic atherosclerosis. CSF flow parameters, such as forward flow volume, forward peak velocity, reverse flow volume, reverse peak velocity, average flow, and net flow volume, were measured with phase-contrast cine MR imaging. Differences between the 2 groups were assessed to determine the independent determinants of these CSF flow parameters.RESULTS: Forward flow volume, forward peak velocity, reverse flow volume, reverse peak velocity, and average flow in the patients with hypertension significantly decreased (all, P < .05). Increasing systolic blood pressure was significantly associated with lower forward flow volume (β = −0.44 mL/mL/mm Hg; 95% CI, −0.83 to −0.06 mL/mL/mm Hg), forward peak velocity (β = −0.50 cm/s/mm Hg; 95% CI, −0.88 to −0.12 cm/s/mm Hg), reverse flow volume (β = −0.61 mL/mL/mm Hg; 95% CI, −0.97 to −0.26 mL/mL/mm Hg), reverse peak velocity (β = −0.55 cm/s/mm Hg; 95% CI, −0.91−0.18 cm/s/mm Hg), and average flow (β = −0.50 mL/min/mm Hg; 95% CI, −0.93 to −0.08 mL/min/mm Hg).CONCLUSIONS: The CSF flow dynamics in patients with hypertension are decreased, and increasing systolic blood pressure is strongly associated with lower CSF flow dynamics.AFaverage flowDBPdiastolic blood pressureFFVforward flow volumeFPVforward peak velocityRFVreverse flow volumeNFVnet flow volumePCC-MRIphase-contrast cine MR imagingPPpulse pressureRPVreverse peak velocitySBPsystolic blood pressure